Optimalisasi Kultur Maggot (Black Soldier Fly) Sebagai Pakan Alternatif Dalam Meningkatkan Pertumbuhan Ikan Budidaya Ramah Lingkungan - Zega, Asokhiwa; Fakta Perjuangan Lombu; Dara Dwista Telaumbanua; Dumasari Telaumbanua; Beriman Gulo; Adeks Kristiani Zebua; Januari Dawolo (Jurnal Perikanan dan Kelautan, 2025)
The high cost of feed is a major challenge in sustainable fish farming. This study aims to examine the optimization of Black Soldier Fly (Hermetia illucens) larvae or maggots as an alternative feed to improve the growth efficiency of environmentally friendly farmed fish. The study employs a quantitative approach through growth tests on catfish (Clarias gariepinus) fed a maggot-based feed formulation produced using various organic waste media. Results indicate that substituting fish meal with maggot meal up to 50% yields significant improvements in daily growth rate and feed conversion efficiency. Maggot culture was also proven to optimally utilize domestic and market organic waste, thereby contributing dual benefits to environmental management. This research underscores the importance of developing local alternative feed for sustainable aquaculture while supporting community-based circular economy initiatives.